Application of Carbon Nanotubes in Breast Cancer Therapy - Tajabadi, Mahdis (Drug Research, 2019)
Conjugated single-walled carbon nanotubes (SWNT) have been shown to be promising in cancer-targeted accumulation and is biocompatible, easily excreted, and possesses little toxicity. The present study aims at reviewing the recent advancements in carbon nanotubes especially SWNT for improving the treatment of breast cancer. Nanotube drug delivery system is a potential high efficacy therapy with minimum side effects for future tumor therapy with low doses of drug.
Keywords: carbon nanotubes; breast cancer cell line